Strategic management to optimize response to cardiac resynchronization therapy registry. (3rd October 2022) - Garcia Bolao, I; Gras, D; D'Onofrio, A; Mark, G; Nair, D; Lellouche, N; Novak, M; Lo, R; Chew, E; Wright, D; Kaplan, A; Veraghtert, S; et al.
Abstract: Background: Cardiac resynchronization therapy (CRT) is guideline-recommended for the treatment of symptomatic heart failure (HF) in patients (pts) with reduced LVEF and prolonged QRS. Clinical trials report Clinical Composite Score (CCS) response rates from 60 to 75%. However, patients with common comorbidities, such as atrial fibrillation, are often under-represented in clinical trials. The Strategic MAnagement to optimize response to cardiac Resynchronization Therapy (SMART) Registry (NCT03075215) was designed to examine outcomes in CRT patients in the real world. Methods: The SMART Registry was a global, multicenter, prospective, clinical registry that enrolled subjects undergoing a de novo CRT-D implant or upgrade from pacemaker to CRT-D using a quadripolar LV lead. CCS was assessed at 12 months post-implant. Results: For study design and CCS outcomes see Figure 1. CCS at 12 months showed that 58.8% of pts improved and 20.1% stabilized. Of the 21.1% of pts that worsened, 8.4% were due to death, 7.8% non-fatal heart failure event, and 5% worsening of NYHA or patient global assessment. Notably, this registry had a high prevalence of pts with NYHA I/II (51%), Non-LBBB (50%), AF (37%), diabetes (35%), and bradycardia (31%) at baseline. Age (>65), diabetes, ischemia, non-LBBB, atrial fibrillation (AF) and renal dysfunction correlated with worsened CCS outcomes. NYHA III/IV patients had significantly higher HF hospitalization (HFH) rates than NYHA I/II (P-value <0.001) (Figure 2a) and patients with AF had higher HFH rates than those without (P-value <0.001) (Figure 2b). Similar effects of NYHA score and AF were seen on mortality. The use of ACE/ARB, or ARNI, and MRA correlated with better outcomes, whereas diuretics and anticoagulants correlated with poorer outcomes. Conclusions: In this large registry, clinical outcomes across important sub-populations are in line with expectations, with older age, ischemia, renal dysfunction, AF, non-LBBB, and diabetes associated with a lower likelihood of response to CRT. By including these patients, this study provides a clearer picture of the effectiveness of CRT in the real world. Future studies should examine optimization approaches to facilitate CRT effectiveness in these under studied patient populations. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): This registry was funded by Boston Scientific (BSC)